2000
DOI: 10.1038/73786
|View full text |Cite
|
Sign up to set email alerts
|

A general definition of metabolic pathways useful for systematic organization and analysis of complex metabolic networks

Abstract: A set of linear pathways often does not capture the full range of behaviors of a metabolic network. The concept of 'elementary flux modes' provides a mathematical tool to define and comprehensively describe all metabolic routes that are both stoichiometrically and thermodynamically feasible for a group of enzymes. We have used this concept to analyze the interplay between the pentose phosphate pathway (PPP) and glycolysis. The set of elementary modes for this system involves conventional glycolysis, a futile c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
644
0
6

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 846 publications
(658 citation statements)
references
References 37 publications
8
644
0
6
Order By: Relevance
“…In this connection, Young and coworkers 16,17 drew on the concept of elementary flux modes, first propounded by Clarke 18 referring to various routines in the network through which external substrate is converted into various fermentation products and biomass. Further, Young and coworkers 16,17 has resolved other difficulties with the cybernetic formulation of large networks by (i) decomposing the pathways into elementary flux modes as done by Schuster et al, 19,20 (ii) by generalizing cybernetic laws using optimal control theory as shown in Young and Ramkrishna 21 to include more general objective functions, and (iii) by incorporation of global objectives such as maximizing biomass or substrate uptake rate among the various modes and to further control of reactions in each mode to enforce the maximum flux throughput. The resulting models are robust and capable of describing dynamic behavior of multiple strains as shown by Young and coworkers.…”
Section: Introductionmentioning
confidence: 99%
“…In this connection, Young and coworkers 16,17 drew on the concept of elementary flux modes, first propounded by Clarke 18 referring to various routines in the network through which external substrate is converted into various fermentation products and biomass. Further, Young and coworkers 16,17 has resolved other difficulties with the cybernetic formulation of large networks by (i) decomposing the pathways into elementary flux modes as done by Schuster et al, 19,20 (ii) by generalizing cybernetic laws using optimal control theory as shown in Young and Ramkrishna 21 to include more general objective functions, and (iii) by incorporation of global objectives such as maximizing biomass or substrate uptake rate among the various modes and to further control of reactions in each mode to enforce the maximum flux throughput. The resulting models are robust and capable of describing dynamic behavior of multiple strains as shown by Young and coworkers.…”
Section: Introductionmentioning
confidence: 99%
“…Hereby, flux balance analysis can highlight the most efficient pathway through the network in order to achieve the particular objective function. Elementary flux mode analysis systematically enumerates all independent minimal pathways through a network, each a unique elementary mode, that are stoichiometrically and thermodynamically feasible [70]. All possible steady-state flux distributions through the metabolic network are nonnegative linear combinations of the set of elementary modes [71].…”
Section: Stoichiometric Modelingmentioning
confidence: 99%
“…An EFM corresponds to a minimal set of reactions that can operate at steady state, thereby using all irreversible reactions in the appropriate direction 1. Here minimal means that no reaction can be removed from the set without losing the ability to form a non‐zero steady‐state flux.…”
Section: Introductionmentioning
confidence: 99%